Sacral Neuromodulation: Foray into Chronic Pelvic Pain in End Stage Endometriosis - Maija Lavonius; Pia Suvitie; Pirita Varpe; Heikki Huhtinen (Case Reports in Neurological Medicine)
Excision of all endometriotic lesions is the method of choice in the treatment of severe endometriosis resistant to medical therapy. The infiltrating nature of the disease as well as extensive surgery may, however, cause chronic pain that cannot be relieved by either surgery or hormonal treatment. As a pilot treatment, we tested the effect of sacral neuromodulation (SNM) for four endometriosis patients suffering chronic pelvic pain and pelvic organ dysfunction after radical surgical treatment. Three out of four patients reported improvement in their symptoms during the neuromodulation testing period and a permanent pulse generator was installed. After 2.5 years, all three patients report better quality of life and want to continue with SNM.